Malay Civilization of The Lembak Tribe, Bengkulu: Integration of Islam and Local Culture - Ismail Ismail; Azizah Aryati; Mukhamad Hadi Musolin; Wildan Nur Hidayat; Sultan Gholand Astapala; Nafilah Chaudittisreen (Journal of Innovation in Educational and Cultural Research, 2026)
This research departs from the rich and complex Malay culture, so understanding it requires a flexible mindset. Understanding Malay concepts must be done holistically and comprehensively, and one of the characteristics of Malay culture is its inclusive nature. One of them is the Lembak tribe in Bengkulu Province. The Lembak Malay tribe hasa very uniquecharacteristic in playing a role in the spread of Islam; the Lembak tribe has succeeded in maintaining their traditions while adopting other Islamic values. Facts show that the Lembak tribe has a complex social structure with a strong kinship system; this contributes to the way they integrate Islamic teachings into their daily lives. This study uses a qualitative method because it allows researchers to explore complex social phenomena in depth. The results of this study indicate that the Lembak tribe is found in Bengkulu Province; it has close social ties and can integrate Islamic values into daily life. This is evidenced by one of the wedding traditions carried out by the Lembak tribe and theSarafalAnam custom.